Potential Model for Binding Energy of First and Second Row Diatomic Molecules - A. K. Pandey; C.K. Dixit2 (AG Volumes, 2022)
A model-potential method is employed to calculate binding, elastic scattering, and annihilation of positrons for a number of atoms and small nonpolar molecules. The model potential contains one free parameter for each type of atom within the target. Its values are chosen to reproduce existing ab initio positron-atom binding energies or scattering phase shifts.